2016
DOI: 10.1177/1747954115624814
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of National Football League coaching trees and the network they comprise

Abstract: The purpose of this study was to analyze professional football coaches' coaching trees and the network they comprise. Employment histories were collected for head coaches (HCs) in the National Football League (NFL) along with the NFL HCs under whom they served as assistant coaches (ACs) prior to their first NFL HC position and repeated until no new mentors were found. Coaches' win-loss records, championships, and Pro Football Hall of Fame status were obtained. Three themes emerged from data analysis: (a) ''Roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Our experiments showed that, for most coaches, this results in a centrality value primarily determined by the number of seasons they have coached future coaches. The current study extends the existing research on coaching trees, which to date has been primarily concerned with the question of whether success is inherited down (7,8). It gives credit to a hypothetical influence of coaches on future coaches regardless of their explicit success.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our experiments showed that, for most coaches, this results in a centrality value primarily determined by the number of seasons they have coached future coaches. The current study extends the existing research on coaching trees, which to date has been primarily concerned with the question of whether success is inherited down (7,8). It gives credit to a hypothetical influence of coaches on future coaches regardless of their explicit success.…”
Section: Discussionmentioning
confidence: 72%
“…The current study extends the existing research on coaching trees, which to date has been primarily concerned with the question of whether success is inherited down ( 7 , 8 ). It gives credit to a hypothetical influence of coaches on future coaches regardless of their explicit success.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations